SOCIAL WILLINGNESS AND PERCEPTIONS OF SAUDI ADULT POPULATION REGARDING ORTHODONTIC TREATMENT: A CROSS-SECTIONAL STUDY (CAHIERS MAGELLANES-NS, 2025)
This cross-sectional study aimed to investigate the social willingness and perceptions of the adult Saudi population regarding orthodontic treatment. The study surveyed Saudi adults aged 18 years and above from various regions using structured questionnaires. Key variables assessed included awareness, understanding, and experiences with orthodontic treatment, as well as perceptions of the need for treatment and barriers to seeking it. Descriptive and inferential statistics were used for data analysis. The findings revealed that a majority of participants were aware of orthodontic treatment, with a high level of understanding. However, only a minority had undergone orthodontic treatment themselves or within their families. While a significant proportion believed they required orthodontic treatment, various barriers such as cost, lack of awareness, and social acceptance were reported. Gender, education level, and socioeconomic status were found to influence participants' perceptions and experiences related to orthodontic treatment. These findings provide insights into the factors influencing the demand for orthodontic treatment among Saudi adults and highlight the need for targeted interventions to address barriers and improve access to orthodontic care.